2018
DOI: 10.1001/jama.2018.3057
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding for Unproven Stem Cell–Based Interventions

Abstract: Because insurers typically will not pay for unproven stem cell interventions, patients seeking these services must purchase them out-of-pocket or use alternative funding mechanisms such as crowdfunding (ie, using online social networks to solicit donations). 1 Crowdfunding for stem cell interventions raises questions concerning how their benefits and risks are depicted in crowdfunding campaigns. Given the increasing visibility and prevalence of health-related crowdfunding, it is important to understand how suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 6 publications
0
51
0
Order By: Relevance
“…13 The popularity of alternative therapies for cancer creates the potential for unproven and potentially dangerous therapies yielding wasted resources, false hopes, delay of appropriate palliative care, and reduced survival. 13,[16][17][18] Determinants of crowdfunding success Beneficiary demographics, treatment type, the campaigning country, number of donors, fundraising goal, and campaign narrative length were important determinants of funding success.…”
Section: Beneficiary Demographics and Inequities In Crowdfundingmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The popularity of alternative therapies for cancer creates the potential for unproven and potentially dangerous therapies yielding wasted resources, false hopes, delay of appropriate palliative care, and reduced survival. 13,[16][17][18] Determinants of crowdfunding success Beneficiary demographics, treatment type, the campaigning country, number of donors, fundraising goal, and campaign narrative length were important determinants of funding success.…”
Section: Beneficiary Demographics and Inequities In Crowdfundingmentioning
confidence: 99%
“…Moreover, inequity, barriers to access, invasion of privacy, fraud, and dangerous therapies have all been associated with MCF, but are poorly understood. 4,7,[15][16][17][18][19] The goal of this study was to evaluate three important aspects of MCF in different healthcare systems: the cause for turning to crowdfunding, characteristics of beneficiaries and campaigns, and factors associated with funding success. We selected GoFundMe as an ideal environment to study.…”
Section: Introductionmentioning
confidence: 99%
“…One search of GoFundMe campaigns identified 1,059 campaigns for unproven and potentially dangerous medical interventions, including homeopathy or naturopathy for cancer (n = 474), hyperbaric oxygen for brain injury (n = 190), stem cells for brain and spinal cord injuries (n = 281), and long‐term antibiotics for chronic Lyme disease (n = 114) . Other studies have identified campaigns for unproven stem cell interventions for a variety of medical needs …”
Section: Articlementioning
confidence: 99%
“…4 Other studies have identified campaigns for unproven stem cell interventions for a variety of medical needs. 5 Recently, GoFundMe prohibited campaigns for antivaccination groups on the grounds that they "promote misinformation about vaccines" and for treatment at a German clinic offering unproven cancer treatments due to "the need to make sure people are equipped to make well-informed decisions." 6 Despite these recent actions to prohibit crowdfunding campaigns that spread medical misinformation or undermine informed medical decision-making, GoFundMe has not taken any additional actions to regulate the much larger presence of campaigns seeking to fund unproven medical interventions on its platform.…”
mentioning
confidence: 99%
“…A research letter in the Journal of the American Medical Association last week noted that patients are often encouraged to raise the money for treatment through crowdfunding on platforms such as GoFundMe and YouCaring 1. These funding campaigns serve to spread the clinics' treatment claims, serving as free direct-to-consumer advertising, the researchers found 1…”
mentioning
confidence: 99%